The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.13168/agg.2016.0035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seasonal hydrologic variations in the La Plata basin from GRACE monthly solutions with in situ gauge water level data

Abstract: Seasonal hydrologic variations have been determined in the La Plata basin from GRACE monthly solutions for a time span of less than 6 years. The results have been compared to tide gauge water level data along several rivers of the La Plata basin. Annual and semi-annual curves have been fitted both to the GRACE water storage variation series and to the tide gauge water level series, correlations between the original series and the curves have been determined, relationship of the amplitudes and phases have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
1
Order By: Relevance
“…The absence of the annual mass variations despite of the seasonality of the rainfall patterns can be originated in complex hydrologic processes. In one of our previous study, we have found that the lack of seasonal water mass variations is typical in the most of the La Plata basin due to the presence of massive dams, waterfalls and the Guarani aquifer (Kiss and Földváry, 2017). The ENSO events have the opposite effect compared to Canada.…”
Section: Analysis Of Multi-annual Mass Variationsmentioning
confidence: 80%
“…The absence of the annual mass variations despite of the seasonality of the rainfall patterns can be originated in complex hydrologic processes. In one of our previous study, we have found that the lack of seasonal water mass variations is typical in the most of the La Plata basin due to the presence of massive dams, waterfalls and the Guarani aquifer (Kiss and Földváry, 2017). The ENSO events have the opposite effect compared to Canada.…”
Section: Analysis Of Multi-annual Mass Variationsmentioning
confidence: 80%
“…A GRACE küldetése során hónapról hónapra új modell meghatározására volt lehetőség, ami alapján a tömegeloszlás időbeli változásának hónapos mintavételezésű vizsgálata végezhető. Bár a hónapos adatmennyiség a nehézségi erőteret csak durva, több száz km-es felbontásban szolgáltatja, ezek kiválóak nagyobb területek éves periódusú (Kiss-Földváry 2015, 2017b és hosszú, akár több évtizedes lefolyású (Földváry-Mészáros 2009, Földváry 2012, Földváry et al 2015, Kiss-Földváry 2017a) tömegátrendeződéssel járó folyamatainak elemzésére és követésére. A GRACE-FO célja a GRACE által megkezdett hónapos idősor folytatása volt, amely (egyéves megszakítással ugyan) lehetővé teszi a vizsgált geofizikai és geodinamikai folyamatok folytatólagos követését (Földváry 2019).…”
Section: Bevezetésunclassified
“…These two missions provide a unique tool for determining the temporal variations of gravity; consequently, the mass redistribution processes that have generated the gravity changes [4]. GRACE and GRACE-FO have become essential sources of data when monitoring the variation in water fluxes over large basins (e.g., the Mediterranean Sea [5], the Arabian Peninsula [6][7][8], Niger [9], Michigan [10], the Amazonas [11][12][13], the La Plata basins [14,15], the Nubian and Nile basins [16][17][18][19][20][21]), and for the analysis of climate changes via ice mass balance [22][23][24], sea level rise [25,26], ground water storage [27][28][29][30][31], and extreme precipitation [32]. In the present study, a GRACE-and GRACE-FO-based gravity anomaly time series is determined and utilized to analyze the desiccation process of the Aral Sea.…”
Section: Introductionmentioning
confidence: 99%